Obesity as a coefficient in the aggravation of patients affected by COVID-19 (Research, Society and Development, 2020)
Objective: To demonstrate through systematic review the relationship between obesity and the new coronavirus, as well as to produce theoretical considerations on this subject. Methods: Systematic review research using search indexes in the electronic databases and portals PubMed and Virtual Health Library (BVS). The data were analyzed using tables and discussed according to the current and relevant literature. Results: Ten articles that met the defined criteria were selected. It was observed that obesity is related to other prevalent comorbidities in patients with COVID-19, such as systemic arterial hypertension and diabetes mellitus, as well as being associated with higher rates of hospitalizations in intensive care units and the use of invasive mechanical ventilation. It is believed that complications arising from obesity in patients with COVID-19 may be related to the cytokines present in the chronic inflammation state characteristic of obese patients. Conclusion: Obesity is related to worse outcomes in patients hospitalized with COVID-19. However, further primary studies are needed to elucidate the degree of influence of obesity in the context of patients with COVID-19.